The Role of E-money on Business Growth in Indonesia - Harril Brimantyo; Agung Suwandaru; Anandhayu Mahatma Ratri; Ginanjar Indra Kusuma Nugraha; Muhammad Rizki Firdaus (Jurnal Bisnis dan Manajemen, 2021)
The objective of this research are to analyze the differences in business growth in Indonesia before and after the e-money, era and to analyze the the role of e-money in business growth in Indonesia.The type of this research is quantitative with comparative and explanatory method. The data used in this research is e-money and Indonesia Composite Index (also known as IHSG). Data analysis technique used in this research are paired t-test and regression. The result shows that there is significant difference of business growth in Indonesia between before and after e-money era. Furthermore, based on regression analysis shows that e-money has significant effect on business growth in Indonesia.